The projects of walk towards the school for the knowledge of the environment and to favor the healthy attitudes and habits from childhood education - Roberto Silva Piñeiro (Pontificia Universidad Católica del Perú, 2018)
Currently a majority of children do not go to school alone, which means that they do not reach some skills that favor autonomy and social interaction. The world authorities are motivating safe and healthy environments around the school, because for decades they have had positive results in several countries. Spanish kindergardens and primary education schools are recognized as appropriate places to experience and knowledge of the environment through physical activity and play. Among the projects on an active school environment, those related with the road to the school are relevant, normally promoted by local governments, with the close collaboration of the school. In any similar proposal, it is as important to pay attention to the educational community like as urban spaces. The walk to the school, which takes place at least twice a day, can be done on foot or by bicycle, which can be a fabulous and modifiable alternative to increase the daily physical activity of children and adolescents, because it helps them to improve their physical health (strength, aerobic endurance, balance, coordination and agility), social relationships and personal skills. The idea of the project walking to school is an initiative that tries to educate to the society into active displacements and sustainable urbanism, with examples all over the world. In any case, the protagonist of the walk to the school is the student, who will learn to move safely and by their own means, and to reflect on classroom activities on mobility and environmental improvement.